2004
DOI: 10.1176/appi.ajgp.12.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Oxidative DNA Damage in the Hippocampus of Elderly Patients With Chronic Schizophrenia

Abstract: Our data provide evidence for oxidative DNA damage and coordinated cell-cycle activation in elderly "poor-outcome" schizophrenia. These findings could have important implications for cellular metabolism, gene expression, and membrane functioning in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…A recent study found increased levels of phosphorylated histone variant H2AX, an index of DNA double strand breaks, in cultured lymphoblasts from schizophrenia patients compared to healthy controls, and an attenuated activation of the same marker after cell irradiation in patients (Catts et al, 2012). In a post-mortem study, an increased intra-neuronal 8-oxodG immunoreactivity in the hippocampus of elderly, poor-outcome schizophrenia patients was observed (Nishioka and Arnold, 2004). However, to our knowledge, this study provides the first evidence for increased systemic DNA and RNA oxidation in vivo in schizophrenia.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study found increased levels of phosphorylated histone variant H2AX, an index of DNA double strand breaks, in cultured lymphoblasts from schizophrenia patients compared to healthy controls, and an attenuated activation of the same marker after cell irradiation in patients (Catts et al, 2012). In a post-mortem study, an increased intra-neuronal 8-oxodG immunoreactivity in the hippocampus of elderly, poor-outcome schizophrenia patients was observed (Nishioka and Arnold, 2004). However, to our knowledge, this study provides the first evidence for increased systemic DNA and RNA oxidation in vivo in schizophrenia.…”
Section: Discussionmentioning
confidence: 94%
“…A smaller collection of studies has been published in relation to markers of DNA damage in schizophrenia. A post-mortem study examining the hippocampi of patients with ' poor outcome ' schizophrenia and non-psychiatric controls, found a ten-fold higher presence of neuronal 8-hydroxy-2'-deoxyguanosine (8-OhdG) among the patients compared with controls, which correlated with elevated quantities of a cell-cycle activation marker (Ki-67) (Nishioka and Arnold, 2004). One study reported a trend increase in lymphocyte DNA damage in schizophrenia patients compared with control subjects , but another found no difference, although those with schizophrenia showed a non-significant increase in sensitivity to externally induced DNA damage and decrease in DNA repair efficiency (Psimadas et al, 2004).…”
Section: Assays Of Oxidative Productsmentioning
confidence: 99%
“…Immunohistochemistry for 8-OHdG formation 8-OHdG immunoreactivity in the mouse brain was examined as described previously 23,24) . Briefly, paraffin sections (6 µm thickness) were incubated with mouse monoclonal anti-8-OHdG antibody (4 µg/ml) (Japan Institute for the Control of Aging, Fukuroi, Japan) overnight at room temperature.…”
Section: Measurement Of 8-ohdg Formation In the Brainmentioning
confidence: 99%
“…The immunostained sections were examined under a microscope. A histopathological study was performed after hematoxylin and eosin staining of paraffin sections as described previously 23) .…”
Section: Measurement Of 8-ohdg Formation In the Brainmentioning
confidence: 99%